Epizoic diatoms on female olive ridley (Lepidochelys olivacea) sea turtles in spawning state at Playa Ventura, Guerrero, Mexico - Díaz Vargas, Migdalia; Carrasco Leandro, Pedro Fabián; Jiménez Piedragil, César Daniel; García Rogríguez, Judith; García Flores, Alejandro; Arce Uribe, Elsah; Muñiz Corona, Yirdael (Acta Universitaria, 2022)
Sea turtles can be a place of settlement for smaller organisms called epibionts, which are harmless guests with a unique relationship. The objective of this study was to identify the diatoms that inhabit the shell of female turtles (Lepidochelys olivacea) during the nesting season 2015-2016 in Playa Ventura, Guerrero, Mexico. A total of 46 female olive ridley sea turtles were sampled from October to January, registering 20 species and 17 genus of diatoms. The genus with the highest number of species were Gomphonema (three species) and Cocconeis (two species). The results indicate that the acquisition and proliferation of diatoms are not directly related to the behavior of the turtles, but rather to each single turtle and their habits.